Oxidized low‐density lipoprotein stimulates epithelial sodium channels in endothelial cells of mouse thoracic aorta. (13th June 2017) - Liang, Chen; Wang, Qiu‐Shi; Yang, Xu; Niu, Na; Hu, Qing‐Qing; Zhang, Bao‐Long; Wu, Ming‐Ming; Yu, Chang‐Jiang; Chen, Xiao; Song, Bin‐Lin; Zhang, Zhi‐Ren; Ma, He‐Ping
Abstract : Background and Purpose: The epithelial sodium channel (ENaC) is expressed in endothelial cells and acts as a negative modulator of vasodilatation. Oxidized LDL (ox‐LDL) is a key pathological factor in endothelial dysfunction. In the present study we examined the role of ENaC in ox‐LDL‐induced endothelial dysfunction and its associated signal transduction pathway. Experimental Approach: Patch clamp techniques combined with pharmacological approaches were used to examine ENaC activity in the endothelial cells of a split‐open mouse thoracic aorta. Western blot analysis was used to determine ENaC expression in the aorta. The aorta relaxation was measured using a wire myograph assay. Key Results: Ox‐LDL, but not LDL, significantly increased ENaC activity in the endothelial cells attached to split‐open thoracic aortas, and the increase was inhibited by a lectin‐like ox‐LDL receptor‐1 (LOX‐1) antagonist (κ‐carrageenan), an NADPH oxidase inhibitor (apocynin), and a scavenger of ROS (TEMPOL). Sodium nitroprusside, an NO donor, diminished the ox‐LDL‐mediated activation of ENaC, and this effect was abolished by inhibiting soluble guanylate cyclase (sGC) and PKG. Ox‐LDL reduced the endothelium‐dependent vasodilatation of the aorta pectoralis induced by ACh, and this reduction was partially restored by blocking ENaC. Conclusion and Implications: Ox‐LDL stimulates ENaC in endothelial cells through LOX‐1 receptor‐mediated activation of NADPH oxidase and accumulation of intracellular ROS. Since the stimulation of ENaC can be reversed by elevating NO, we suggest that both inhibition of ENaC and an elevation of NO may protect the endothelium from ox‐LDL‐induced dysfunction. Linked Articles: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc